Customers driving a firm's responsible innovation response for grand challenges : A co-active issue-selling perspective - Degbey, William Y.; Pelto, Elina; Öberg, Christina; Carmeli, Abraham (Product Development and Management Association, 2023)
Grand challenges vary across industries and call for firms to craft a responsible innovation response to effectively address them. However, key questions concerning why firms embrace responsible innovation and the process by which they respond to grand challenges have yet to be fully answered. We integrate an issue-selling theoretical lens and the customer role from an innovation perspective to theorize about the different influencing motives that customers exert on their corresponding supplying firm to craft a more responsible innovation response to grand challenges. Based on qualitative data collected in almost a 10-year period from multiple respondents across eight customer firms and two supplying firms, we identify three core motives—regulatory, business opportunity, and socio-environmental motives—that propel customers to influence supplying firms to craft different forms of responsible innovation responses. Our research also reveals three vital socio-human capital pathways—human capital, socio-behavioral, and relationship—which, in turn, foster a co-active engagement in addressing grand challenges innovatively and responsibly. In so doing, this research advances novel theorizing on co-active engagement in responsible innovation where the customer acts as the primary champion and the supplier as the implementer. We discuss the important implications for customers and other stakeholders.
Keywords: co-active engagement; grand challenges; issue selling; responsible innovation; sustainability; fi=Henkilöstöjohtaminen|en=Human Resource Management|